2007
DOI: 10.1080/08958370701628721
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular and Genomic Response of an Immortalized Microglia Cell Line (BV2) to Concentrated Ambient Particulate Matter

Abstract: Ambient particulate matter (PM) damages pulmonary tissue through oxidative stress (OS) pathways. Several reports indicate that the brain is another affected target of PM exposure. Since microglia (brain macrophages) are critical to OS-mediated neurodegeneration, the cellular and genomic response of immortalized mouse microglia (BV2) was examined in response to fine ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…Interestingly, microglia exposed in vitro to concentrated ambient air pollution upregulate mRNA of pro-inflammatory cytokines, such as IL-1β and TNFα 91, suggesting that some forms of PM may be able to cause cytokine production. Further, there is evidence that metals associated with air pollution activate microglia, as microglia are activated in vitro by manganese94, a component of industrial-derived air pollution.…”
Section: Cellular Mechanisms Of Neuroinflammationmentioning
confidence: 99%
“…Interestingly, microglia exposed in vitro to concentrated ambient air pollution upregulate mRNA of pro-inflammatory cytokines, such as IL-1β and TNFα 91, suggesting that some forms of PM may be able to cause cytokine production. Further, there is evidence that metals associated with air pollution activate microglia, as microglia are activated in vitro by manganese94, a component of industrial-derived air pollution.…”
Section: Cellular Mechanisms Of Neuroinflammationmentioning
confidence: 99%
“…Particulates can be transported along the axons, bypassing the blood‐brain barrier, and cross the synaptic cleft into the brain parenchyma . Based on in vitro evidence, the pollutants may activate microglial via toll‐like receptor signaling, inducing an inflammatory response and oxidative stress . Thus, the neurotoxicity of inhaled particulate matter (collected from a public park in Tuxedo, NY, and concentrated) is exacerbated in apolipoprotein E null rats, which are systemically prone to oxidative stress …”
Section: Environmentalmentioning
confidence: 99%
“…Consistent with human reports (13), animal studies have revealed that exposure to diverse forms of outdoor air pollution by inhalation, such as urban particulate matter (34, 35), O 3 (36), diesel exhaust (3739), and manganese (40, 41), results in elevated cytokines and oxidative stress in the brain. More specifically, several inhaled air pollutants are shown to activate microglia with direct effects in vitro (38, 42, 43), in animal models (38, 44), and in human (13) studies.…”
mentioning
confidence: 99%